Pengaruh Musa acuminata Cavendish Subgroup (Pisang Ambon) Dalam Menurunkan Tekanan Darah - Aprilia Susanti; Fitria Eka Resti; Reni Purbanova (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2019)
Hypertension is a public health problem that happens a lot, many people do not realize that they suffer from hypertension, this is due to symptoms that are not real and in the early stages before causing serious health problems, new symptoms are clearly visible at age 50- an. Generally there have been more severe complications or diseases such as a heart attack or stroke. Because of its presence which is still difficult to detect and control, it is not surprising that hypertension has been dubbed the